2017
DOI: 10.1002/jmor.20701
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular distribution of calcium during spermatogenesis of zebrafish, Danio rerio

Abstract: Calcium plays a variety of vital regulatory functions in many physiological and biochemical events in the cell. The aim of this study was to describe the ultrastructural distribution of calcium during different developmental stages of spermatogenesis in a model organism, the zebrafish (Danio rerio), using a combined oxalate-pyroantimonate technique. Samples were treated by potassium oxalate and potassium pyroantimonate during two fixation stages and examined using transmission electron microscopy to detect ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 56 publications
(71 reference statements)
2
12
0
Order By: Relevance
“…The main objective of this study was to evaluate the effects of calcium deprivation and calcium (Nano particles and commercial) administration on male rat reproductive functions. Multiple investigations have shown that Ca 2+ plays a major role in sperm control and fertilization events [41,42]. Our results revealed a significant decrease in serum calcium, testosterone hormone and ABP levels in Ca 2+ -deficient group as a consequence of receiving purified rat protein diet deficient in calcium for 64 days, on the other hand it revealed a significant increase in their levels in serum of Nano and commercial calcium administered male rats.…”
Section: Discussionsupporting
confidence: 48%
“…The main objective of this study was to evaluate the effects of calcium deprivation and calcium (Nano particles and commercial) administration on male rat reproductive functions. Multiple investigations have shown that Ca 2+ plays a major role in sperm control and fertilization events [41,42]. Our results revealed a significant decrease in serum calcium, testosterone hormone and ABP levels in Ca 2+ -deficient group as a consequence of receiving purified rat protein diet deficient in calcium for 64 days, on the other hand it revealed a significant increase in their levels in serum of Nano and commercial calcium administered male rats.…”
Section: Discussionsupporting
confidence: 48%
“…In studies on annual gonadal cycle of fish, it is crucial to examine gonadal cycle and spawning pattern (Tan-Fermin et al, 1997;Manosroi et al, 2003;Golpour et al, . 2017Niksirat et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that calcium signaling is also involved in spermatogenesis, sperm function, and fertilization, essential processes for male reproduction [1]. Calcium ions are stored in spermatogenic cells at various developmental stages, and also in Leydig and Sertoli cells [2]. The concentration of calcium in spermatogenic cells gradually increases from the early to late stages of spermatogenesis (spermatogonia < spermatocytes < spermatids < spermatozoa), and the concentration of calcium ions in seminiferous tubules also varies in different sections [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Calcium ions are stored in spermatogenic cells at various developmental stages, and also in Leydig and Sertoli cells [2]. The concentration of calcium in spermatogenic cells gradually increases from the early to late stages of spermatogenesis (spermatogonia < spermatocytes < spermatids < spermatozoa), and the concentration of calcium ions in seminiferous tubules also varies in different sections [2,3]. Calcium signaling in Leydig cells regulates the production of steroids through nuclear receptors and emergency response proteins mediated by a transcription cascade [4].…”
Section: Introductionmentioning
confidence: 99%